Monkey See, Monkey Do Otherwise: Interpolation in Maxine Hong Kingston’s Tripmaster Monkey: His Fake Book - Lestari Manggong (Unipdu Jombang, 2020)
A descendant of Chinese immigrant living in San Francisco, Wittman Ah Sing—the main character in Tripmaster Monkey, the personification of a simian figure Sun Wu-k’ung from the classic tale The Journey to the West—represents the idea of a “melting pot” gone burst. With two cultures (Chinese and American) bubbling in his veins, Wittman is chameleon-like in terms of projecting his image. Just like Sun Wu-k’ung, Wittman interposes, intervenes, and interjects a wide range of counter-discursive tactics into the dominant discourse. This essay argues that Wittman fits into the category of what postcolonial theory calls ‘interpellated subject’ (Althusser, 1970). As such, Wittman, in his reactions, interpolates (Ashcroft, 2001) or writes back the various modes of hegemonic discourse, to counter its effects by transforming them. This essay thus tackles with the problematization of Wittman’s hybridity, ranging from what this quality contributes to the narrative structure of the novel to the way it affects the complexity of how Wittman sees things. Throughout his journey in the West, Wittman only expects to see what he wants to see, the way he would like to see it. In addition, he sees things as metaphors, which is an indication of an effect of having two (or more) cultures and ideologies on each lens of his spectacles. As a result, unlike the monkey in children’s mimic game Monkey See Monkey Do, Wittman the tripmaster monkey in this instance, suffers from an inability to mimic what he sees accordingly.